Quantifying Interactions among European Equity Markets with Time-Varying Conditional Skewness - Twomey, Cian E (Archives of Business Research, 2018)
This paper explores the influence of global and regional factors on the conditional distribution of daily stock returns in four European markets – the U.K., Germany, France, and Spain - using factor models in which unexpected returns comprise global, regional and local shocks. Besides conditional heteroscedasticity, the model innovates by allowing shocks to incorporate time-varying conditional skewness, which is found to increase the explanatory power of our modelling. The relative importance of the global and regional factors varies across the four markets, with the largest, most international market (the U.K.) being more dependent on global factors as compared to the regional importance for the Spanish market. Also, the global factor is relatively less important for market volatility in models that permit time-varying conditional skewness.